The U.S. Women's Soccer Team : an American success story - Lisi, Clemente A. (Scarecrow Press, 2010)
On a July afternoon in 1999, this country's proudest moment in soccer occurred in Pasadena, California. In the presence of more than 90,000 fans and viewed by another 40 million watching on television, the United States women outlasted China to win the World Cup. Though it has lagged far behind in regard to the men's game, the United States was at the forefront when it came to women's soccer. In The U.S. Women's Soccer Team: An American Success Story, Clemente A. Lisi looks at how the sport has gained popularity over the last couple of decades. While other books have written about the team du.